2022
DOI: 10.1186/s43159-022-00185-0
|View full text |Cite
|
Sign up to set email alerts
|

Physical growth and social prognosis of esophageal atresia after 15 years of age

Abstract: Background The mortality rate of esophageal atresia (EA) has significantly improved, but late complications remain problematic. We evaluated the physical growth, late complications, and social prognosis of postoperative patients with EA who have reached 15 years of age. Methods EA patients who were treated at our institution from 1984 to 2003 were enrolled. The follow-up, physical growth at the last visit, late complications and treatment, academic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…Long-time follow-up demographic data is scarce for patients born with EA. According to a recent study, EA patients still have a lower mean z-score for body weight (− 1.4) and height (− 0.7) in adolescence around the age of 15 [ 21 ]. One study reported that 75% of 13-year-old patients had a normal nutritional status, 16% were obese and 9% were malnourished [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Long-time follow-up demographic data is scarce for patients born with EA. According to a recent study, EA patients still have a lower mean z-score for body weight (− 1.4) and height (− 0.7) in adolescence around the age of 15 [ 21 ]. One study reported that 75% of 13-year-old patients had a normal nutritional status, 16% were obese and 9% were malnourished [ 22 ].…”
Section: Discussionmentioning
confidence: 99%